Behavioral Presentation, Clinical Management, and Outcome of Maternal Rejection in Mares: A Retrospective Case Series of 27 Cases - Paula Nistor; Ionica Iancu; Vlad Iorgoni; Alexandru Gligor; Alexandru Ciresan; Bogdan Florea; Vlad Cocioba; Cosmin Horatiu Maris; Viorel Herman (Veterinary Sciences, 2026)
Maternal rejection is an uncommon postpartum behavioral disorder in mares that may compromise colostrum intake, mare–foal successful nursing acceptance, and neonatal survival. This retrospective observational study described the clinical presentation, therapeutic management, and short-term outcome of 27 mares diagnosed with maternal rejection between September 2023 and June 2026 in western Romania. Data regarding breed, parity, parturition, behavioral presentation, treatment, supportive management, time to maternal acceptance, and outcome were extracted from medical records. Associations between categorical variables were evaluated using Fisher’s exact test, while differences in time to acceptance were assessed using the Mann–Whitney U test. Primiparous mares represented 59.3% of cases, and obstetrical complications occurred in 48.1%. Aggressive behavior was the predominant presentation. Primiparous mares exhibited aggressive forms of rejection significantly more frequently than multiparous mares (p = 0.006) and required a significantly longer interval before maternal acceptance (median: 38 h versus 21 h; U = 117.0, p = 0.010). Oxytocin was the most frequently administered medication, and behavioral management accompanied pharmacological treatment in most cases. Maternal acceptance was achieved in 24 of 27 mares (88.9%). Early recognition and individualized multimodal management may contribute to favorable short-term outcomes.